2010
DOI: 10.1590/s0102-311x2010000800001
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão arterial sistêmica no Brasil: tendência temporal

Abstract: The first temporal trend curve on proportional mortality in Brazil was published in 1984 (1930-1980) (Bayer GF, Paula SG. RADIS Dados 1984; 7:1-8), causing widespread surprise due to the decline in mortality from infectious and parasitic diseases and the rapid rise in mortality from cardiovascular diseases. The curves had crossed in 1964-1965, shifting the country's main morbidity and mortality epidemiological profile from diseases of underdevelopment to diseases of modernity. As a silent condition, systemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
1
4
0
7
Order By: Relevance
“…The prevalence measured by Vigitel is compatible with other self-reported studies in the country 8,9,12,14 . Regional differences were pointed out and, in some capitals, prevalence rates are very different.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The prevalence measured by Vigitel is compatible with other self-reported studies in the country 8,9,12,14 . Regional differences were pointed out and, in some capitals, prevalence rates are very different.…”
Section: Discussionsupporting
confidence: 90%
“…In order to correct the potential vices due to the low coverage of households with landlines, Vigitel used the cell weighing method according to sex, age and schooling, therefore adjusting the distribution of the sample to the characteristics of the population REV BRAS EPIDEMIOL SUPPL PeNSE 2014; 215-226 living in each capital (according to the census by IBGE). With that, it was possible to reduce the differences between population with and without landlines 14,31 . Other comparative studies between data from Vigitel and household surveys indicated the importance of weighing to reduce vice in some variables, especially those associated with low income and low schooling 32,35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foram excluídos aqueles indivíduos cujas informações relacionadas à queixa de zumbido e/ ou problemas de saúde estavam incompletas, que A Hipertensão Arterial (HA) é um distúrbio circulatório, considerado crônico, assintomático e de origem multifatorial, caracterizado pela presença de elevados níveis de pressão sanguínea 5 . No Brasil, estima-se que mais de 30% da população seja hipertensa, podendo chegar a mais de 50% após os 60 anos 6 .…”
Section: Métodounclassified